Tourist Accomodation: A Host-Tourist Matched for Batur Geotourism - Ernawati, Ni Made; Arjana, I Wayan Basi; Sitawati, Anak Agung Raka (Graduate School, Universitas Brawijaya, 2019)
This article presents research results on tourist accommodation available in Batur geotourism: a host-tourist approach. It is developed based on a documentary study. There are four main studies on Batur conducted earlier which reports were assessed that are relevant to discover the match of tourist needs and the availability of tourist accommodation in Batur geotourism area. This qualitative research using secondary data which was conducted in an effort to find a solution to the issue of a short tourist stays in Batur. The assessment results show three matched types of accommodation that highly compatible between guest-accommodation available in Batur and tourists' needs for accommodation. These includes homestay covering basic and functional accommodation; moderate standard accommodation including the villa, guest house, and two/three-star hotel; and luxury accommodation inclusive tourist attractions comprising boutique hotel. This concludes that the short tourist stays in the area is not due to the unavailability of accommodation. Further assessment is required to discover the solution to the matter. The problems might lie on the lack of information and promotion or the limited tourist attractions and activities available in Batur; that require further action from the management of Batur tourism as well as the government of Bangli Regency to address the issue. It is expected that these study results could be used as a reference by Batur geotourism management to further develop the area. Keywords: Accommodation, Community-based tourism, Geotourism, Geotourism products, Geotourists, tourist stays.